I am trying to understand if

$$\sqrt{\frac{2\pi}{1-x}}-\sum\limits_{k=1}^\infty\frac{x^k}{\sqrt{k}}$$ is convergent for $x\to 1^-$. Any help?

Update: Given the insightful comments below, it is clear it is not converging, hence the actual question now is to find

$$ \lim_{x\to 1^-}\left(\sqrt{\frac{\pi}{1-x}}-\sum_{n\geq 1}\frac{x^n}{\sqrt{n}}\right)$$

  • 1
    $\begingroup$ And... what did you try? $\endgroup$ – Did May 17 '16 at 12:56
  • 2
    $\begingroup$ Are you sure $\sqrt{\frac{2\pi}{1-x}}$ is not meant to be $\sqrt{\frac{\pi}{1-x}}$? As you have it at the moment the coefficients of $x^n$ differ by a factor of approx $\sqrt2$ for large $n$. $\endgroup$ – almagest May 17 '16 at 13:09
  • 1
    $\begingroup$ I think the stirling formula helps. $\endgroup$ – user90369 May 17 '16 at 13:11
  • 4
    $\begingroup$ Notice $\displaystyle\;\sum_{k=1}^\infty \frac{x^k}{\sqrt{k}} = {\rm Li}_{1/2}(x)$ where ${\rm Li}_s(x)$ is the Polylogarithm function. We have $${\rm Li}_s(e^\mu) = \Gamma(1-s)(-\mu)^{s-1} + \sum_{k=0}^\infty \frac{\zeta(s-k)}{k!} \mu^k \quad\text{ for }\quad |\mu| < 2\pi,\; s \ne 1, 2, 3,\ldots $$ This implies $$\lim_{x\to 1^{-}} \left(\sqrt{\frac{\pi}{1-x}} - \sum_{k=1}^\infty\frac{x^k}{\sqrt{k}}\right) = -\zeta(1/2) \approx 1.460354508809586812889499... $$ $\endgroup$ – achille hui May 17 '16 at 14:52
  • 1
    $\begingroup$ @JackD'Aurizio technically, this doesn't answer the question as it is not a proof. $\endgroup$ – achille hui May 17 '16 at 14:55

Following the comment posted by @Achillehui, we recognize that the series $\sum_{k=1}^\infty \frac{x^k}{\sqrt{k}}$ is a series representation of the polylogarithm function $\text{Li}_{1/2}(x)$, for $|x|<1$.

An alternative series representation (SEE HERE) of $\text{Li}_{1/2}(x)$ is given by

$$\text{Li}_{1/2}(x)=\sqrt{\frac{\pi}{-\log(x)}}+\sum_{k=0}^\infty \frac{\zeta(1/2-k)}{k!}\log^k(x) \tag 1$$

for $|x|<e^{2\pi}$.

Note that we can expand the logarithm function around $x=1$ as

$$\begin{align} -\log(x)&=(1-x)\left(1+\sum_{k=2}^\infty\frac{(-1)^{k-1}(x-1)^{k-1}}{k}\right)\\\\ &=(1-x)\left(1+O\left((x-1)\right)\right) \tag 2 \end{align}$$

Using $(2)$ in $(1)$, we obtain

$$\text{Li}_{1/2}(x)=\sqrt{\frac{\pi}{1-x}}++\zeta(1/2)+O\left(\sqrt{1-x}\right)+\sum_{k=1}^\infty \frac{\zeta(1/2-k)}{k!}\log^k(x) \tag 3$$

Finally, it is easy to see from $(3)$ that

$$\lim_{x\to 1^-}\left(\sqrt{\frac{\pi}{1-x}}-\sum_{k=1}^\infty \frac{x^k}{\sqrt{k}}\right)=-\zeta(1/2)$$

And we are done!

  • $\begingroup$ (+1) How to prove that asymptotic expansion, however, is a tougher problem than the OP's one :) $\endgroup$ – Jack D'Aurizio May 17 '16 at 16:34
  • 1
    $\begingroup$ @JackD'Aurizio Jack, that is for certain. First, we start with an integral representation of $\text{Li}_s(z)$ and deform the Hankel contour. Then, we evaluate that integral as a series of residues. Finally, we fold the series, expand the binomial coefficients, change the order of summation, carry out the inner sum, and arrive at the coveted expression. -Mark $\endgroup$ – Mark Viola May 17 '16 at 16:49

In order to make user90369's (excellent and elementary) answer a real answer, we have to show that $$\lim_{x\to 1^-}\sqrt{1-x}\sum_{n\geq 1}\frac{x^n}{\sqrt{n}}=\sqrt{\pi}\tag{1}$$ or: $$ \lim_{x\to 1^-} (1-x)\sum_{m\geq 2}\left(\sum_{n=1}^{m-1}\frac{1}{\sqrt{n}\sqrt{m-n}}\right)x^m=\pi\tag{2} $$ but that follows from the same argument it is usually exploited to prove Hilbert's inequality, namely that for large $m$s, $$ \sum_{n=1}^{m-1}\frac{1}{\sqrt{n}\sqrt{m-n}}=\frac{1}{m}\sum_{n=1}^{m-1}\frac{1}{\sqrt{\frac{n}{m}}\sqrt{1-\frac{n}{m}}}\approx \int_{0}^{1}\frac{dx}{\sqrt{x}\sqrt{1-x}}=\pi.\tag{3} $$ If we set $f(x)=\sum_{n\geq 1}\frac{x^n}{\sqrt{n}}$ and $h(x)=\sqrt{\frac{\pi}{1-x}}$, $(1)$ alone is not enough to ensure that $h(x)-f(x)$ is bounded in a left neighbourhood of $x=1$. However, the study of the Taylor coefficients is:

$$\begin{eqnarray*}h(x)-f(x)&=&\sum_{n\geq 1}\left(\frac{\sqrt{\pi}}{4^n}\binom{2n}{n}-\frac{1}{\sqrt{n}}\right)x^n\\&=&\sum_{n\geq 1}\left(\frac{\Gamma\left(n+\frac{1}{2}\right)}{\Gamma(n+1)}-\frac{1}{\sqrt{n}}\right)x^n\\&\ll&\sum_{n\geq 1}\frac{1}{n\sqrt{n}}\ll 1\tag{1bis}\end{eqnarray*} $$ by Gautschi's inequality. Now we may exploit an analytic continuation. $$ f(x)=\sum_{n\geq 1}\frac{x^n}{\sqrt{n}} = \sum_{n\geq 1}\frac{(-1)^{n+1} x^n}{\sqrt{n}}+2\sum_{n\geq 1}\frac{x^{2n}}{\sqrt{2n}}=g(x)+\sqrt{2}\,f(x^2)$$ hence: $$ g(x)=\sum_{n\geq 1}\frac{(-1)^{n+1} x^n}{\sqrt{n}} = f(x)-\sqrt{2}\,f(x^2)\tag{4}$$ while $h(x)=\sqrt{\frac{\pi}{1-x}}$ fulfills: $$ h(x)-\sqrt{2}\,h(x^2) = h(x)\left(1-\sqrt{\frac{2}{1+x}}\right) \tag{5}$$ hence:

$$\begin{eqnarray*} \lim_{x\to 1^-}\left(h(x)-f(x)\right) &=& \frac{1}{1-\sqrt{2}}\lim_{x\to 1^-}\left[h(x)-\sqrt{2}\,h(x^2)-f(x)+\sqrt{2}\,f(x^2)\right]\\&=&\frac{1}{\sqrt{2}-1}\lim_{x\to 1^-}g(x)\\&=&\frac{1}{\sqrt{2}-1}\sum_{n\geq 1}\frac{(-1)^{n+1}}{\sqrt{n}}=\color{red}{-\zeta\left(\frac{1}{2}\right)}. \tag{6}\end{eqnarray*}$$

  • 1
    $\begingroup$ To square, interesting , thank you ! $\endgroup$ – user90369 May 17 '16 at 15:21
  • 1
    $\begingroup$ Leakages from a talented mathematician... $\endgroup$ – guest May 17 '16 at 15:32
  • $\begingroup$ So your (1) to (3) should be deleted... I dont see any connection between them and the real solution...And is the zeta function continuous at 1/2, I'm not very familiar with zeta functions... $\endgroup$ – Peter May 17 '16 at 15:48
  • $\begingroup$ @Yongyong: $(1)$ is necessary to make $(3),(4),(5)$ actually work, and to prove $(1)$ I used $(2)$ and $(3)$, so no, they cannot be deleted. And if you are not that confident with the $\zeta$ function, you may simply ignore the very last expression: the answer is given by a (slowly) convergent series. $\endgroup$ – Jack D'Aurizio May 17 '16 at 15:50
  • 1
    $\begingroup$ your result $(1)$ reminds me of the formula $$\lim_{x \to 1^{-1}}\sqrt{1 - x}(x + x^{4} + x^{9} + \cdots) = \int_{0}^{\infty}e^{-x^{2}}\,dx$$ +1 $\endgroup$ – Paramanand Singh May 18 '16 at 7:36


$g(x):= \sqrt{\frac{2\pi}{1-x}}-f(x)$

$\sum\limits_{k=1}^\infty (-1)^{k-1} \frac{x^k}{\sqrt{k}}=f(x)-\sqrt{2}f(x^2)$ is convergent for $x\uparrow 1$ .


$\sum\limits_{k=1}^\infty (-1)^k \frac{x^k}{\sqrt{k}}+\sqrt{\frac{2\pi}{1-x}}-\sqrt{2}\sqrt{\frac{2\pi}{1-x^2}}= g(x)-\sqrt{2}g(x^2)$.

For $x\uparrow 1$ we get $\sum\limits_{k=1}^\infty (-1)^k \frac{1}{\sqrt{k}}=(1-\sqrt{2})g(1)$.

Therefore is the limit $g(1)=\frac{1}{\sqrt{2}-1}\sum\limits_{k=1}^\infty (-1)^{k-1} \frac{1}{\sqrt{k}}$.

EDIT: See above, it's not $\sqrt{2\pi}$, it's $\sqrt{\pi}$

Thank you all for your efforts!

EDIT 2: $g(1)=-\zeta(\frac{1}{2})$

  • $\begingroup$ When $\sqrt{2\pi}$ really comes into play? $\endgroup$ – Jack D'Aurizio May 17 '16 at 14:49
  • $\begingroup$ A very good question ! I only assume, that $g(1)$ is $<\infty$, but than it works. Why ? $\endgroup$ – user90369 May 17 '16 at 14:52
  • $\begingroup$ @Jack D'Aurizio: It seems to be that I don't proof, THAT there is a limit. But IF a limit exits, THEN its $g(1)$. Therefore my question is still opened, you are right. $\endgroup$ – user90369 May 17 '16 at 15:02
  • $\begingroup$ I just added a proof of the "missing part" in your argument. Now your answer with my prologue gives an elementary alternative to achille hui's technique (asymptotics for $\text{Li}_s$). $\endgroup$ – Jack D'Aurizio May 17 '16 at 15:18
  • $\begingroup$ I know, thanks again! $\endgroup$ – user90369 May 17 '16 at 15:41

Using the binomial series you know that $\sqrt{\frac{2\pi}{1-x}}=\sqrt{2\pi}+\sum_{k=1}^\infty\begin{pmatrix}-\frac{1}{2}\\k\end{pmatrix}(-x)^k=\sqrt{2\pi}+\sqrt{2\pi}\sum_{k=1}^\infty \frac{(2k)!}{4^k(k!)^2}x^k$. Using Stirling's formula you know that $\sqrt{2\pi}\frac{(2k)!}{4^kk!}=\frac{\sqrt{2\pi}}{4^k}(1+\epsilon_k)\frac{\sqrt{2\pi(2k)}(\frac{2k}{e})^{2k}}{(\sqrt{2\pi k}(\frac{k}{e})^{k})^2}=(1+\epsilon_k)\frac{\sqrt{2}}{\sqrt{k}}$, where $\epsilon_k\rightarrow 0$ as $k\rightarrow\infty$. Now compare this to $\frac{1}{\sqrt{k}}$, for $k$ large enough, the kompnents of the sum is for instance larger than $\frac{1}{3\sqrt{k}}$, Then the sum is $\geq C+\sum_{k>N}\frac{1}{3\sqrt{k}}x^k$. The right hand side goes to infinity as $x\rightarrow 1$ form left side.

I think the problem would be more interesting if we have $\sqrt{\pi}$ in the first komponent, then it seems that one should modify $\epsilon_k$ to obtain the rate, but this not clear for me, at least this is not readable from the given Stirling's formula.

  • $\begingroup$ Thank you for your efforts! $\endgroup$ – user90369 May 17 '16 at 14:53

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.